New Zealand : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix describes New Zealand's evolving approach to inflation targeting. It describes the experience of New Zealand with inflation targeting, and discusses the motives behind the change in its approach toward a more flexible framework. The paper discusses the main features of New Zealand's exchange rate cycle during the 1990s. It also analyzes some of the potential causes of exchange rate variability, and describes the effects of variability on other macroeconomic variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet